Core/Shell Nanostructures: Etching‐Free Epitaxial Growth of Gold on Silver Nanostructures for High Chemical Stability and Plasmonic Activity (Adv. Funct. Mater. 34/2015). (September 2015) - Liu, Hongpo; Liu, Tingzhuo; Zhang, Lei; Han, Lu; Gao, Chuanbo; Yin, Yadong
Abstract : An etching‐free epitaxial growth method is developed to convert Ag nanostructures of various morphologies into their Ag@Au core/shell counterparts. Anisotropic ones such as nanoplates exhibit excellent plasmonic properties and chemical stability, as shown on page 5435 by C. Gao, Y. Yin and co‐workers. As a result, the core/shell structures display high activity and reliability in many plasmon‐based applications, such as chemical sensing by surface‐enhanced Raman spectroscopy.